1990
DOI: 10.1007/bf01194177
|View full text |Cite
|
Sign up to set email alerts
|

Do phytoseiid mites select the best prey species in terms of reproductive success?

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 19 publications
1
22
1
2
Order By: Relevance
“…Two func-tional arguments would predict the opposite, a preference for apple rust mite: (1) the predator's intrinsic rate of increase is higher when fed apple rust mites exclusively than when fed European red spider mites exclusively (Dicke et al 1989a). (2) Under selective feeding the time needed to find and catch a prey is longer than when both prey species are accepted.…”
Section: Functional Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Two func-tional arguments would predict the opposite, a preference for apple rust mite: (1) the predator's intrinsic rate of increase is higher when fed apple rust mites exclusively than when fed European red spider mites exclusively (Dicke et al 1989a). (2) Under selective feeding the time needed to find and catch a prey is longer than when both prey species are accepted.…”
Section: Functional Analysismentioning
confidence: 99%
“…The amount needed is small: females that feed on a carotenoid source can supply their offspring with enough carotenoids for diapause induction (Van Zon et al 1981). Both P. ulmi and A. schlechtendali may provide the predators with carotenoids ( Van der Geest 1985;Dicke et al 1989a). However, Dicke et al (1989a) observed that these two prey species are not identical in this respect.…”
Section: Pyri Prefers P Ulmi?mentioning
confidence: 99%
See 2 more Smart Citations
“…Alguns estudos têm demonstrado que certas espécies de Euseius podem se desenvolver e reproduzir alimentandose apenas de eriofídeos (Dicke et al 1990, Schausberger 1992.…”
unclassified